Implementation of Social Communication in the Recovery of Drug Abuse Victims - Muhammad Hambali; Muniruddin Muniruddin (LPPM Universitas PGRI Sumatera Barat, 2024)
Drug abuse is a big problem in society because its impact can affect many aspects of life. Apart from harming the people directly affected, this also has an impact on families and society as a whole. Facing this challenge, new recovery methods are starting to be developed, especially those involving social and spiritual communication, to help victims of drug conservation. This research aims to evaluate the use of spiritual social communication methods in the recovery of drug abuse victims at the Bhayangkara Indonesia Drug Abuse Prevention Rehabilitation Center, Medan. Using a qualitative approach based on case studies, this research examines the influence of social spiritual communication methods on the recovery process, the challenges that arise, and strategies to increase their effectiveness. Research methods include participant observation, in-depth interviews with drug abuse victims and rehabilitation facilitators, as well as analysis of documents related to rehabilitation programs. The research results show that the integration of socio-spiritual communication methods has a positive impact on the recovery of victims. However, implementing this method faces several obstacles such as lack of community support and limited resources. To overcome these challenges, efforts are needed to increase public understanding and support, provide adequate resources, and strengthen professional capabilities in spiritual guidance. The conclusion of this research is that with shared commitment, social-spiritual communication methods can be an important element in sustainable recovery for victims of drug abuse.